Rethinking rights historical, political, and philosophical perspectives - Frohnen, Bruce; Grasso, Kenneth L. (Eric Voegelin Institute series in political philosophy., 2009)
"Essays retrace the historical development of rights in the West, assessing the influence of Locke, Burke, and the authors of the Declaration of Independence to clarify the experience of rights within the Western tradition, showing that rights need to be rethought so that they may again truly serve the human good"--Provided by publisher.